2021
DOI: 10.3389/fcell.2021.711352
|View full text |Cite
|
Sign up to set email alerts
|

The Vital Roles of LINC00662 in Human Cancers

Abstract: Long non-coding RNAs (lncRNAs) play crucial roles in many human diseases, particularly in tumorigenicity and progression. Although lncRNA research studies are increasing rapidly, our understanding of lncRNA mechanisms is still incomplete. The long intergenic non-protein coding RNA 662 (LINC00662) is a novel lncRNA, and accumulating evidence suggests that it is related to a variety of tumors in multiple systems, including the respiratory, reproductive, nervous, and digestive systems. LINC00662 has been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…LEMD1-AS1 is reported to act as a prognostic signature for ovarian cancer [ 40 ], while AL031667.3 and AC019080.5 are proven to be capable of predicting the outcome of lung adenocarcinoma [ 41 ]. LINC00662 is shown to promote the development and progression of cancer and have relationships with a wide range of tumors in various systems [ 42 ], such as the reproductive, respiratory, and nervous systems. However, the functional mechanism of the other MRLs have rarely been studied and remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…LEMD1-AS1 is reported to act as a prognostic signature for ovarian cancer [ 40 ], while AL031667.3 and AC019080.5 are proven to be capable of predicting the outcome of lung adenocarcinoma [ 41 ]. LINC00662 is shown to promote the development and progression of cancer and have relationships with a wide range of tumors in various systems [ 42 ], such as the reproductive, respiratory, and nervous systems. However, the functional mechanism of the other MRLs have rarely been studied and remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, long noncoding RNA LINC00662 was demonstrated to be able to up-regulate the expression of WNT3A by binding to miR-15a/16/107, activate Wnt/β-catenin signaling, and further promote the proliferation and growth of HCC cells in vivo . At the same time, WNT3A induces the polarization of M2 macrophages in a paracrine manner 32 - 34 (Figure 3 ) .…”
Section: The Immune Network In Tme Of Hccmentioning
confidence: 88%
“…Furthermore, overexpression of LINC00662 has also been observed in other types of tumors, including breast, cervical, and prostate cancers and chordoma, glioma, and hepatocellular carcinoma [39]. LINC00662 has been shown to participate in regulating mRNA stability as a mediator of gene expression, and to participate in different signaling pathways [39]. Unfortunately, the ncRNA-eQTL database does not include specific information on lncRNA-eQTLs for GBC; however, some of our validated lncRNA-eQTLs are linked to other cancer types [40].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis in gastric cancer suggested that LINC00662 overexpression is tightly related to poor patients' prognosis [38]. Furthermore, overexpression of LINC00662 has also been observed in other types of tumors, including breast, cervical, and prostate cancers and chordoma, glioma, and hepatocellular carcinoma [39]. LINC00662 has been shown to participate in regulating mRNA stability as a mediator of gene expression, and to participate in different signaling pathways [39].…”
Section: Discussionmentioning
confidence: 99%